ANALISIS PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, PENGETAHUAN TEKNOLOGI, KEPERCAYAAN TERHADAP PERILAKU PENGGUNA MOBILE BANKING DENGAN MEDIASI ANIMO TRANSAKSI - Nicholas Nicholas; Hommy Dorthy Ellyany Sinaga; Sri Rezeki (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
This study aims to determine the effect of Ease of Use, Technology Knowledge, and Trust either partially or simultaneously on Transaction Interest, to determine the effect of Transaction Interest on User Behavior, and to determine the effect of Interest Transaction on mediate the effect each X variable to Y.This research uses descriptive and quantitative methods and data sources in the form of primary and secondary data. The population in the research were all customers in 2022. A total sample was 95 customers with a tolerable error rate of 10%. The sampling technique with nonprobability sampling uses the type of insidental sampling. Data were analyzed using the multiple linear regression analysis method which resulted in the Equation of Interest Transaction = -12.718 + 0.241easy of use + 0.483technology knowledge + 0.755trust and User Behavior = 8,599+ 0,426 transaction interest. The results showed that the Ease of Use partially had a positive and significant effect on the Transaction Interest. Technology Knowledge partially had a positive and significant effect on the Transaction Interest. Trust has a positive and significant effect on the Transaction Interest. Transaction Interest had a positive and significant effect on the User Behavior. Based on the results of simultaneous hypothesis testing, it is known that the results of the F test show that the Ease of Use, Technology Knowledge, and Trust variables simultaneously affect the Transaction Interest. Sobel test results show that Transaction Interest had not mediate effect of all free variables on User Behavior variable. The amount of adjusted R Square on first equation is 0.550 or 55%, which means that the Ease of Use, Technology Knowledge, and Trust affect the Interest Transaction by 55% and the amount of adjusted R Square on second equation is 0,307 or 30,7% which means that Transaction Interest affect the User Behavior by 30,7%.